Basaloid (Cloacogenic) Carcinoma Mimicking Intraabdominal Abscess: Report of a Case and Review of the Literature - Akbulut, Sami (S. Karger AG, 2009)
Cloacogenic carcinoma (CC, basaloid carcinoma) generally occurs around the dentate line, rarely it can arise from the other sides of the colon. There are only 5 cases of CC located outside the anal canal in the literature. The first occurrence of a CC presents as intraabdominal abscess. We describe a 23-year-old male patient who was admitted with fever and severe abdominal pain. Computed tomography imaging showed diffuse wall thickening about 10–11 cm above the rectosigmoid junction, intraabdominal abscess and a soft tissue lession covering the pelvis with a size of 8 × 8.5 cm including cystic necrotic areas. We performed Hartman procedure since the mass was nonresectable. Histopathological examination showed CC. In total, three times radiotherapy and a concurrent three-drug regimen of irinotecan, fluorouracil and folinic acid chemotherapy were administered for 6 weeks. As a result, the patient was lost because of multiple organ dysfunction syndrome that developed 3 months after radio-chemotherapy.